EMPOWERMENT OF COMMUNITIES ENTERPRISES OF KERINJING OGAN ILIR VILLAGE THROUGH TRAINING AND ASSISTANCE IN THE MANAGEMENT FIELD, FINANCE, AND MARKETING - Maulana, Ahmad; Novalia, Nurkardina; Rosa, Aslamia; Puspita Sari, Dwi Darma; FS Kerlyn, Defebri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This community service activity aims to provide services to MSME actors who want to maintain and develop their businesses amid economic competition and during the Covid-19 Pandemic by maximizing the use of technology in their business. Through the urgency of the MSME needs for digital marketing facilities and financial consulting, as well as the availability of human resources for the service team that can meet the needs of MSME assistance services in Kerinjing Village, Tanjung Raja District, Ogan Ilir Regency from April 2022 to November 2022. This community service activity includes assisting the needs of related MSMEs making online marketing media and making financial reports that are carried out in stages, starting with partner coordination meetings, collecting data on MSME needs and allocation of companions, preparing services, and ending with the implementation of the mentoring process to fulfill MSME needs in Kerinjing Village, Tanjung Raja District, Ogan Ilir Regency. to increase the added value of the business for MSMEs. The outputs of this activity include publications in the Sumatra Express mass media and national journals. Through publications, community service activities become transparent and can continue to become regular MSME service activities to continue to provide solutions to the needs of MSME actors